Sistem Informasi Pengingat Jadwal Imunisasi Pada Anak Usia Dini Menggunakan Metode Scrum Berbasis Android Di Bidan Hana Suroyyah, Am.Keb - Vika Vitaloka Pramansah (E-Jurnal Universitas Samudra, 2022)
Immunization is an effort by the Indonesian government to achieve the Millennium Development Goals (MDGs) which are the focus of reducing the volume of child mortality. The mortality index in children under five is the main parameter to determine the health status of the community, especially children under five. For this reason, the health service program in Indonesia focuses on reducing infant mortality through immunization. However, sometimes parents forget the schedule for the implementation of immunization in the following month so that it is very detrimental to parents, especially the health of toddlers. This study aims to build an information system on the application as a reminder of the immunization schedule for the midwife Hana Suroyyah, Android-based Am.Keb. This research was conducted by going through several stages, namely identifying existing problems, literature study with previous journals, collecting the required data, and developing an immunization schedule reminder information system with SMS Gateway using the scrum method. The information generated in this application is an Immunization Schedule which is equipped with a notification as a reminder of the Immunization schedule before D-1 using an SMS Gateway.